The Technological Properties of Oriental Beech (Fagus orientalis Lipsky) Impregnated with Boron Compounds and Natural Materials - Hakan Adanur; Muhammed Said Fidan; Şekip Şadiye Yaşar (BioResources, 2017)
Impregnation, drying, and varnishing are performed to increase the usage life of wood material by making it resistant to chemical, physical, and biological agents. The most common wood protection procedures are chemical methods. Therefore, it is essential to develop new impregnation substances that do not harm the environment and human health but are still economically efficient. In this study, oriental beech (Fagus orientalis Lipsky) was impregnated with borax and boric acid in 1%, 3%, and 5% aqueous solutions. Quechua (Caesalpinia spinosa) was also used as a natural impregnation substance. The retention amount of the impregnated samples was examined for the oven-dried density, bending strength, elastic modulus, screw holding strength tests, compression strength parallel to the grain, and Bending strength parallel to the grain. The samples impregnated with borax had higher oven-dried density, bending strength, elasticity modulus in bending, and Bending strength parallel to the grain tests than samples treated with boric acid; however, the screw holding strength tests showed the opposite trend. The screw holding strength was higher in the impregnated samples than in controls. The bending strength, the elasticity modulus in bending, and the Bending strength parallel to the grain were lower in the control samples.